“Implementasi Peraturan Daerah (PERDA) Nomor 1 Tahun 2015 tentang Perlindungan dan Pemenuhan Hak Penyandang Disabilitas di SLB-B Kabupaten Wonosobo” - Aga Fakhrur Rozi; Sri Suwitri (Journal of Public Policy and Management Review, 2017)
The implementation of education for disabilities persons is carried out through special education and inclusion with specific curricula and learning processes and learning places, but the role of the Wonosobo regency government tackles this problem less than optimal. This study aims to describe how the implementation of Regional Regulation Number 1 of 2015 on the Protection and Fulfillment of the Rights of Disabilities Persons in extraordinary school of Wonosobo Regency, and to identify the supporting and inhibiting aspects of the implementation of the Regional Regulation. The theory used is the implementation model of George Edward III, Mazmanian and Sabatier, Mazmanian and Sabatier, as well as Meter and Horn theory. The research studied using descriptive research approach. Data collection techniques used in the form of interviews, obervasi and documentation, with qualitative descriptive data analysis. The results show that in general the government, school and community institutions have the same perception toward the principle, purpose and purpose of the law. Protection of persons with disabilities has not fully covered all types of persons with disabilities. Supporting the success of this policy is the environmental aspect with the high level of community support, the policy implementation aspect with the similarity of interests between the government and the community, the support of resources, and the good compliance and responsiveness of the implementers, and the characteristic aspects of the implementing agency with positive responses to policies and commitments the high of the executor. While inhibiting the success of the policy is the communication aspect by the local government and the communication from the community where many people with disability are shut down, the information about the existence of disabled people, and the environmental stagnant in the form of socioeconomic condition of the society which is low. The recommendation of the researcher is the need for better socialization by the government, as well as the effort to establish for Public Extraordinary School of Wonosobo Regency, so that children with disability can be accommodated in special schools that are designated for children with disabilities.